Imagens e histórias em arte terapia: experiências nas interfaces da psicologia, da educação e da arte - Rodrigues, Valeria Elisabete [UNESP] (2015)
This dissertation describes the articulation and the creative process of experiences in art therapy based on transdisciplinary method of knowledge approach, making connections with art in the light of the concept of hybridity (Valente, 2008), with the epistemology of complexity (Morin, 1998) and with the archetypal psychology (Hillman, 2010). The research presents the history of Art Therapy in Brazil to reflect and discuss about the promotion of Social Inclusion through the art (collaborative experiences). The basis of this work comes from the art group ACATE - Atelier Compartilhado de Artes e Terapias Expressivas, which has been born from a partnership between the students of specialization program in Art Therapy/ Expressive Therapies of UNESP - Universidade Estadual Paulista with art students and professors of the same university to create the University Extension Project ArtInclusiva from 2011 March to 2013 March, besides other experiences of the author with art therapy focusing in group works. It also intends to promote reflections and searches through a central question: Can art therapy have art goals? This work is totally justified considering the excellent results in terms of making easily the access to art issues, art education, the promotion of human development and also the psychological changes in all the people involved with the project. The proposal proved to be an important space to train professionals, promoting skills in the people involved with the project; and unique and different proposal with work group and all the facilities available at IA - UNESP. For all this reasons, it deserves to be documented to show or guide transdisciplinary initiatives to create artistic hybrid process or procedure.